Herbal-Based Topical Gel of Impatiens balsamina L. Enhances Macrophage Infiltration in Traumatic Oral Mucosal Ulcer Repair - Arina Shafia; Shalli Herliana Rahmawati; Isa Anshori Muchaeroni (Syntax Corporation Indonesia, 2026)
Traumatic oral mucosal ulcers are common lesions that require effective inflammatory regulation for optimal healing, in which macrophages play a crucial role. Long-term use of topical corticosteroids is associated with adverse effects, encouraging the exploration of safer herbal-based alternatives. Impatiens balsamina L. has demonstrated anti-inflammatory and wound-healing properties; however, evidence regarding its effect on macrophage responses in traumatic oral ulcers remains limited. This research aimed to evaluate the effect of topical Impatiens balsamina L. extract gel on macrophage cell counts during the healing of traumatic oral mucosal ulcers. An in vivo experimental study with a post-test only control group design was conducted using 27 male Wistar rats. Traumatic ulcers were induced on the inferior labial vestibular mucosa and treated topically for three days with either 15% extract gel, 10% extract gel, or gel base (n= 9 per group). Macrophage counts were assessed histologically using Hematoxylin and Eosin staining. Data were analyzed using Welch’s one-way ANOVA followed by the Games–Howell post hoc test. Mean macrophage counts were highest in the 15% extract gel group (111.78 ±15.68), followed by the 10% group (45.00 ±10.56) and the control group (22.22±3.35). Significant differences were observed among all groups (P<0.001). Topical Impatiens balsamina L. extract gel significantly increased macrophage presence during traumatic oral ulcer healing, with the 15% concentration showing superior effectiveness. These findings confirm that Impatiens balsamina L. extract gel accelerates the inflammatory phase of wound healing by enhancing macrophage recruitment, supporting its potential as a natural alternative for oral ulcer management.